The validity and reliability of quality improvement and accreditation system instrument in managing childcare center - Siti Noor Ismail; Faizahani Ab Rahman; Farah Mohamad Zain; Aizan Yaacob (Institute of Advanced Engineering and Science, 2022)
Quality improvement and accreditation system (QIAS) instrument was developed to determine the quality management practices level in childcare centers in Malaysia. This study was conducted in Kedah, Penang, and Kelantan to intricate the reliability and validity of the instrument. Exploratory factor analysis (EFA) and item reliability analysis have been used to measure the level of reliability and authenticity of the questionnaires. Further, inter-rater reliability (IRR) test was used to obtain expert confirmation of the reliability, validity and credibility of the instrument. All the seven constructs possessed high reliability index value between 0.87–0.92. Similarly, EFA analysis showed that there are seven dimensions exist in the QIAS instrument with factor loading ranged from 0.64–0.88. The findings also showed that the variance explained in the data is 64.46% with Eigenvalue more than 1. These results reflecting that all the item are accepted with a high verification. In addition, a very high reliability coefficient value, α=0.93 and inter-rater reliability of 91% indicated a high level of agreement and reliability among field evaluators. The results proved that this QIAS instrument had high validity and reliability and was capable to measure the quality management practices level in Malaysian childcare center.